EKSISTENSI PIDANA MATI DALAM PERSPEKTIF HUKUM PIDANA - Eleanora, Fransiska Novita (MAJALAH ILMIAH WIDYA, 2012)
The issue of capital punishment in Indonesia provided for in Article 10 of the Criminal Code, where there is a difference of opinionbetween the pro and con, because it is contrary to religion and human rights. The purpose of this paper is to discuss whether the deathpenalty still exists in the legislation to be maintained. The method used the research literature study. It can be concluded that the deathpenalty can be accepted by Indonesian society and still exist to be retained by the decision of the Constitutional Court (MK).